Applying the Seven Virtues of a Gentleman to Enhance Goodness - Anuruktrakoon, Natthakit (Journal of Buddhist Studies Chulalongkorn University, 2024)
This article springs from a profound interest in the promotion of goodness. Despite prior applications of ethical principles and legal enforcement, the issue of fraud and corruption remain unresolved. Consequently, I have here chosen to study the Seven Virtues of a Gentleperson to enhance goodness. They delineate the seven fundamental criteria for the recognition of a good person. The research examines relevant literature and presents a thorough analysis of how to implement the Seven Virtues of a Gentleperson. The study reveals that fostering the Seven Virtues of a Gentleperson in individuals may lead to a more virtuous society.The practice of mutual kindness engenders a positive environment, reduces instances of fraud and corruption, and contributes to a more pleasant community within our society.